Desempenho de híbridos, sistemas de condução e aplicação foliar de fungicidas na incidência de grãos ardidos na cultura do milho (Zea mays L.). - Chaves Neto, José Roberto (2016)
The maize is one of the most important cereal grown worldwide. With the advancement of acreage and monoculture, the emergence of several diseases is well known, which has generated losses of quality and productivity of these grains. Among the diseases affecting the corn crop, there is the rot of corn which consequently cause the so-called burning grains, in addition, some of the causative fungi can synthesize mycotoxins that contaminate grain, affecting the quality of these and mainly generating risks animal and human health. In this context the objective of this study is to evaluate the influence of the hybrid, the seeding system, irrigation and foliar application of fungicides in the incidence of fungi that cause the ear rot in corn. The experiments (Experiment I, as irrigation and Experiment II, without irrigation) were installed and conducted in Cruz Alta, RS, in the season 2014/15. The experimental design was randomized blocks in three-factor scheme 2x2x4 corresponding to two hybrids (BG7051H and BG7060HR), two seeding system (direct and conventional) and four treatments (T1: Witness, T2: Pyraclostrobin + Epoxiconazole; T3: Picoxystrobin + cyproconazole; T4: Azoxystrobin + Benzovindiflupir), respectively, in 4 repetitions. The experimental plot had four rows spaced (0.50 m 10.0 m), total area of 20 m2 and floor area of 8 m2, which took place the plant height of reviews and the insertion of the first ear (cm) mass tang (g), number of grains per ear (n), mass of grains per spike (g) of the 1000 seeds (g), grain yield (kg ha-1), incidence of damaged kernels (%) , grain sanity ( "Blotter Test") and in vitro susceptibility of fungi the fungi Penicillium sp., Fusarium spp. and Aspergillus sp. fungicide.